2015
DOI: 10.1007/s00167-015-3891-2
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the shape of the tibial insertion site of the anterior cruciate ligament: classification is required

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 29 publications
0
36
1
2
Order By: Relevance
“…The comparison between our results and those of other authors, by the various modes of evaluation, is found in ►Table 3. [3][4][5][6][7][8][9][10][11][12][13][18][19][20][21][22][23][24] In fact, Lord et al 25 published a study of the function of the ACL tibial insertion fibers in the resistance of anterior and rotational displacements, with robotics, in six degrees of freedom of movement. They concluded that the central, posterior and lateral fibers of the ACL tibial insertion play a secondary role in the restriction of tibial displacements and that the most important fibers are the anterior and the anteromedial peripheral portion.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison between our results and those of other authors, by the various modes of evaluation, is found in ►Table 3. [3][4][5][6][7][8][9][10][11][12][13][18][19][20][21][22][23][24] In fact, Lord et al 25 published a study of the function of the ACL tibial insertion fibers in the resistance of anterior and rotational displacements, with robotics, in six degrees of freedom of movement. They concluded that the central, posterior and lateral fibers of the ACL tibial insertion play a secondary role in the restriction of tibial displacements and that the most important fibers are the anterior and the anteromedial peripheral portion.…”
Section: Discussionmentioning
confidence: 99%
“…The tibial and femoral osseous attachments of the ACL have been widely studied, and despite traditionally having an oval and crescent-like shape respectively, potential variations in their shape have been suggested. 95,96 The anatomical characteristics of the attachments, in conjunction with the tendency to avoid impingement, led to interesting operative concepts, such as the meticulous placement of the ACL graft within the tibial and femoral footprints, i.e. complete footprint restoration.…”
Section: Ideal Position Characteristicsmentioning
confidence: 99%
“…In a recent study of 100 patients, mean age 26 years, undergoing ACL reconstruction, the tibial insertion was elliptical in 51 knees, triangular in 33 knees, and C-shaped in 16 knees. 6 Posterolateral fatty degeneration was observed in 26 knees. Given the smaller number of C-shaped insertion sites in this younger age group, fatty degeneration with aging may explain the C-shaped appearance of some specimens.…”
Section: See Related Article On Page 2101mentioning
confidence: 99%